2015
DOI: 10.1139/cjpp-2014-0509
|View full text |Cite
|
Sign up to set email alerts
|

The unpaved journey of vitamin C in cancer treatment

Abstract: Effectiveness and low-toxicity to normal tissues are ideal properties for a cancer treatment, and one that numerous research programs are aiming for. Vitamin C has long been used in the field of Complementary and Alternative Medicine as a cancer treatment, with profound safety and anecdotal efficacy. Recent studies revealed the scientific basis for this use, and indicated that vitamin C, at supra-nutritional doses, holds considerable promise as an effective and low-toxic therapeutic strategy to treat cancer. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 78 publications
1
28
0
1
Order By: Relevance
“…A potential problem for multi-targeting agents is collateral/ multiple toxicities. However, pharmacological ascorbate is safe with few adverse events in animals and people 55 . Combination of this unique agent with current 1 st line chemotherapy or radiation therapy may result in additional synergistic effects in treating tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A potential problem for multi-targeting agents is collateral/ multiple toxicities. However, pharmacological ascorbate is safe with few adverse events in animals and people 55 . Combination of this unique agent with current 1 st line chemotherapy or radiation therapy may result in additional synergistic effects in treating tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Necorosis, caspase-dependent and caspase-independent apoptosis, and autophagy were reported in ascorbate-induced cell death in different types of cancer (Chen et al, 2015). A recent study by Yun and colleagues demonstrated that vitamin C selectively kills KRAS and BRAF mutant colorectal cancer cells by targeting GAPDH, but spares normal cells (Yun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Ascorbate has been shown to increase the effectiveness of various anticancer treatments. 18,19 Mixed micelles composed of TPGS and AP are nanosized colloidal particles with a hydrophobic core and a hydrophilic corona. The hydrophobic segment forms the core of the micelles that solubilize the hydrophobic drug molecules, and the hydrophilic segment forms the corona that provides compatibility of the micelles in the aqueous environment.…”
Section: Zhang Et Almentioning
confidence: 99%